Naringin derivatives as glucosamine-6-phosphate synthase inhibitors based preservatives and their biological evaluation - Amit Lather (Nature Portfolio, 2020)
Abstract Glucosamine-6-Phosphate synthase enzyme has been targeted for development of better and safe preservative due to its role in microbial cell wall synthesis. In recent year’s demand of preservatives for the food, cosmetics and pharmaceuticals have increased. Although, the available synthetic preservatives have associated unwanted adverse effects, soa chain of naringin derivatives were schemed synthesized and judged for antioxidant, antimicrobial, preservative efficacy, stability study and topical evaluation. Molecular docking resulted with excellent dock score and binding energy for compound 7, compound 6 and compound 1 as compared to standard drugs. Resultant data of antimicrobial activity revealed compound 7as most potent antimicrobial compound for P. mirabilis, P. aeruginosa, S. aureus, E. coli, C. albicans, and A. niger, respectively, as compared to the standard drugs. The preservative efficacy test of compound 7 in White Lotion USP showed the log cfu/mL value within prescribed limit of USP standard. Compound 7 stabilize the White lotion USP from microbial growth for a period of six months under accelerated storage condition. Compound 7 was further evaluated for toxicity by using the Draize test in rabbits and showed no sign of eye and skin irritation. The outcome demonstrated that synthesized naringin compounds showed glorious antioxidant, antimicrobial, preservative efficacy, stable and safe as compared to standards.